2017
DOI: 10.1155/2017/4532320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fatty Liver on Acute Pancreatitis Severity

Abstract: Aim. Acute pancreatitis is typically a mild disease, but some patients develop severe courses. Fatty liver changes are seen in patients with acute pancreatitis, but its clinical significance has not been well-studied. We aimed to investigate the relationship between fatty liver and the severity of acute pancreatitis. Methods. Unenhanced CT images of patients with acute pancreatitis were retrospectively reviewed by a radiologist, and mean hepatic and splenic attenuation was measured in Hounsfield units (HU). Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Sensitivity analysis, except for one outcome, showed no significant difference. When we removed the study of Yoon et al [ 37 ] from the forest plot with the odds of pancreatic pseudocyst, the results became non-significant (OR = 2.09; CI: 0.97–4.55).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Sensitivity analysis, except for one outcome, showed no significant difference. When we removed the study of Yoon et al [ 37 ] from the forest plot with the odds of pancreatic pseudocyst, the results became non-significant (OR = 2.09; CI: 0.97–4.55).…”
Section: Resultsmentioning
confidence: 96%
“…Guidelines recommend performing a contrast-enhanced CT scan within 72 h–96 h after the onset of the AP symptoms [ 6 ]. Combined unenhanced and enhanced CT scans may be useful in assessing the status of both AP and FLD [ 37 ]. Studies that used CT scan and US or other methods (US elastography, MRI, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies on the association between fatty liver and AP, namely with the severity of AP [81]. Yoon et al [95], in their study investigating the relationship between fatty liver and the severity of AP, verified that fatty liver may play a prognostic role in this disease and could be incorporated into future predictive scoring models.…”
Section: Fatty Livermentioning
confidence: 99%
“…It was suggested that CT plain scan should be completed within 12 hours after emergency treatment to evaluate the extent of exudation of pancreatitis. At the same time, other acute abdomen can also be dis-International Journal of Clinical Medicine tinguished [1]. By morphological features, the range of peripancreatic fluid accumulation and pancreatic necrosis can be effectively distinguished.…”
Section: Discussionmentioning
confidence: 99%